Management of Less-Than-Severe Aortic Stenosis During Coronary Bypass: A Systematic Review and Meta-Analysis. Issue 4 (July 2019) - Yanagawa, Bobby; An, Kevin R.; Ouzounian, Maral; Gaudino, Mario; Puskas, John D.; Asaoka, Nozomi; Verma, Subodh; Friedrich, Jan O.
Abstract : Objective: The management of concomitant mild-to-moderate aortic stenosis (AS) at the time of coronary artery bypass graft (CABG) is controversial. Here we perform a systematic review and meta-analysis of CABG and aortic valve replacement (AVR) versus CABG alone in patients with mild–moderate AS. Methods: We searched MEDLINE and EMBASE databases until July 2018 for studies comparing CABG & AVR versus CABG in patients with mild–moderate AS undergoing coronary bypass. Data were extracted by 2 independent investigators. The main outcomes were operative mortality, long-term survival, and reintervention for AS. Results: There were 6 unmatched retrospective observational studies with 1, 172 patients (median follow-up 4.7 [interquartile range: 4.3 to 5.3] years). Patients undergoing CABG & AVR had less severe coronary artery disease. There were no differences in operative mortality (relative risk [RR]: 1.07; 95% CI, 0.59 to 1.94; P = 0.8). CABG & AVR was associated with greater incidence of stroke, bleeding, renal failure, and mediastinitis. At median follow-up of 5 years, there was no difference in long-term mortality (incidence rate ratio [IRR]:1.44; 95% CI, 0.83 to 2.51; P = 0.19), but CABG & AVR was associated with 73% lower risk of reoperation for AS ( n = 13/485 versus n = 71/702; IRR: 0.27; 95% CI, 0.14 to 0.51; P < 0.001). Conclusions: In patients undergoing CABG with mild–moderate AS, combining AVR with CABG was associated with no difference in operative mortality but with increased risk of stroke, bleeding, renal failure, and mediastinitis. Long-term mortality was not different, but a risk of reoperation for AS at 5 years was 73% lower. Given the increasingly wide availability and safety of transcatheter aortic valve replacement (TAVR), one may consider a conservative approach toward concomitant mild–moderate AS.